Halal preneurs = Keusahawanan Halal - Abdullah, Moha Asri (2018)
Much has been discussed on entrepreneurship. Scholars have researched a huge amount of literature on successful entrepreneurs. With a fast-growing halal industry and sharp rising global demand for halal food and beverages, halal pharmaceutical, halal cosmetics and tourism and hospitalities, halalpreneurs has been of special focus lately. However, there is evidently difficult to define halapreneurs, their scope, and their successful ventures. This talk is about how halalpreneurs is defined, what was a historical development of halalpreneurs and to what extent their prospects and opportunities in the market nationally and globally.